Variation in the provision of chemotherapy for colorectal cancer. Issue 12 (1st December 1999) - McLeod, A
Abstract : OBJECTIVE: To quantify the impact of patient, area and hospital characteristics on variations in the provision of chemotherapy for colorectal cancer. SUBJECTS: Incident cases of colorectal cancer (ICD 153-154), aged under 75 years and resident in Scotland, derived from linked hospital discharge records and death records for the period January 1990 to June 1994. The final analysis was carried out on 7852 patients resident in 823 areas and first admitted to one of 59 hospitals. MAIN OUTCOME MEASURE: Whether a patient received chemotherapy (OPCS4 procedure code X35.2) during any hospital episode in the six months after their first admission. METHODS: Multilevel logistic regression to separate effects of patients, areas and hospitals. RESULTS: During the study period, 8% (n = 626) of the study population received chemotherapy within six months of their first admission. Adjusting for comorbidities and emergency admissions, both age and deprivation were significantly associated with the treatment. The odds ratios (OR) of chemotherapy relative to patients aged 65-74 were 2.13 and 4.50 for patients aged 55-64 and under 55 respectively. Relative to patients resident in the most affluent areas, the OR of chemotherapy for patients resident in the most deprived areas was 0.73. Area level availability of the treatment was not significantly associated with a patient's odds of receiving the treatment while on site provision of chemotherapy at the hospital of first admission was (OR = 4.32). There was significant unexplained variation between hospitals of first admission but not between areas of residence; between hospital variation decreased by 22% during the study period. CONCLUSION: Differences according to age may reflect both clinical and patient decisions regarding the benefits of the treatment relative to its toxicity. Lower treatment rates in deprived areas may indicate inequitable access to services. Hospital differences may reflect consultant effects and it would be expected that these should decrease now that the efficacy of the treatment has been recognised and guidelines have been issued.